Konflik Plasma Sawit dan Politik Klientelisme di Desa Tanjung Labu Pulau Lepar - Irawan, Hosea Alfandi; Robing, Robing (Journal of Politics and Democracy, 2025)
This study examines the agrarian conflict in Tanjung Labu Village, Lepar Island, triggered by the oil palm company’s unfulfilled obligation to provide 20 percent of plantation land as plasma since 2001. What initially emerged as an agrarian justice issue has gradually shifted into a political instrument repeatedly mobilized in village head elections. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and document analysis. The findings reveal that the plasma issue has been systematically politicized as an electoral commodity. Village head candidates employ the promise of plasma to attract community support, yet once elected they tend to soften their stance and even accommodate corporate interests. This recurring pattern highlights the operation of clientelistic politics at the village level, where promises of land redistribution are reduced to symbolic capital without substantive realization. The agrarian politics framework explains the structural inequalities underlying the conflict, while clientelism theory and the concept of local elites elucidate how the plasma issue is mediated and reproduced within the logic of village politics. The study concludes that the plasma conflict in Tanjung Labu is not merely a symptom of failed agrarian policy but has been institutionalized as a political asset that stabilizes elite power while obstructing substantive conflict resolution.